Ultrasound-assisted liquid–liquid spray extraction for the determination of multi-class trace organic compounds in high-volume water samples. Issue 19 (16th August 2018) - Kaw, Han Yeong; Li, Junlin; Jin, Xiangzi; Wang, Zhao; Cong, Linlin; He, Miao; Li, Donghao
Abstract : A premier analytical method for the determination of multi-class trace organic compounds in high-volume water matrices. Abstract : In order to extract trace organic compounds (TrOCs) from large volumes of water (over 10 L), an ultrasound-assisted liquid–liquid spray extraction (UA-LLSE) technique is proposed. The UA-LLSE integrates liquid–liquid extraction, spray atomisation and ultrasonication in a single step. Under an acoustic field, a water sample is continuously spray injected into an extracting organic solvent to generate numerous water microdroplets in the organic phase. As a result, the extraction time and efficiency are significantly improved through increasing the interactive surface area, collision probability and mass transfer between two liquid phases. Other major parameters affecting the extraction efficiency such as nozzle type, spray angle, flow rate, nozzle position, ultrasonication energy, and extraction cycle were optimised. This newly developed technique has been applied to determine the trace organic compounds in real-world environmental matrices, and the results were compared with the results of the conventional liquid–liquid extraction method. For the analysis of high-volume water samples, UA-LLSE is a simple, inexpensive, time-saving (20 min for 10 L of water sample) and environmentally friendly method (reduction in solvent usage), with high extraction efficiency (over 90% average recoveries) and excellent precision (lower than 7% relative standard deviation, RSD). Most importantly, it is an ideal on-site pre-treatment technique for the in situ extraction of trace organic compounds in high-volume water matrices.